BIFURCATION OF PERIODIC SOLUTION FROM AN EQUILIBRIUM POINT IN THE MULTIPARAMETER CASE (Journal of Sciences, Islamic Republic of Iran)
We consider the bifurcation of periodic solutions from an equilibrium point of the given equation: x =F(x,?) , where x ? R , ? is a vector of real parameters ? , ? , ... , ? and F:R x R ->R has at least second continuous derivations in variables